Praktik Self-Tracking di Media Sosial Pemuda pada Transisi Menuju Dunia Kerja - Mutiara Nur Hayati (Jurnal Studi Pemuda, 2022)
This study explores the strategies and efforts that have been made against the risks of using social media for fresh graduate who are looking for job. These risks are obtained from personal historical data and surveillance by other parties, especially Human Resources. These strategies and efforts are carried out as individual goals in modifying employable identity or for getting a job. Therefore, the research questions are how fresh graduate treat personal data about themselves that are shared on social media and how digital self-tracking forms the relationship between digital technology and self-identity. Through a qualitative approach using digital ethnographic methods and self-tracking theory by Deborah Lupton, the authors attempt to answer the questions in this study by conducting interviews and observations on six informants who carry two identities, that is fresh graduate and job seekers. This study showed that the informants carried out two strategies on personal historical data: cleaning and displaying. Furthermore, when doing self-tracking, informants also establish relations with digital technology to produce negotiation related to the formation of the expected self-hood, which at the end of the study shows not only the goal of getting a job but also efforts for self-reflection, learning, and growing process.